Development of the Potential of Umbul Tourism Park in Purorejo Village, Lumajang District - Fiki Ramadhan; Gusti Jimmy Murhpy; Agus Mahardiyanto; Arya Majdan Faradis; Laksana Fajar Gumilang; Nadya Fitria Ningsih; Roihanah Roihanah; Reza Eka Wahyuning Firdausyah; Wanti Amiliana; Wiwit Mila Rahayu; Zahra Puteri Ramadhani (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
Tourism plays an important role in increasing the economic level of the Indonesian people and the quality of the country. This effort can be carried out by emphasizing the importance of the existence of an independent village, so that the village can maximize the potential of its natural and human resources through one of the representations of community-based tourism development, namely through tourism villages. Purorejo Village, which is in Tempursari District, Lumajang Regency, East Java Province, is a village that has tourism potential, such as springs, waterfalls, and streams. The tour that is superior in Purorejo Village is the Umbul Sari spring tour. This study aims to develop the tourism potential of Umbul Tourism Park in Purorejo Village, Lumajang Regency through photo spot competitions and master plan designs. The research method used in this activity is a site survey, discussion, branding, and master plan design. The results showed that designing a master plan by students was one of the solutions for rebuilding the Umbul Tourism Park tour and training on digital marketing for the Umbul Tourism Park tourism marketing division could help market this tour and reach a wider market share.